A Metastatic Malignant Peripheral Nerve Sheath Tumor with Its Imaging Features - Saloni Rajkotia; Ritesh Suthar; Abhishek Palsapure; Jahnavi Gandhi (Swiss Journal of Radiology and Nuclear Medicine)
Malignant peripheral nerve sheath tumors (MPNST) are rare and aggressive soft tissue sarcomas arising from the peripheral nerves. These tumors are associated with neurofibromatosis type 1 (NF1), and though they can occur sporadically, their diagnosis can be complex, especially when metastases are present. This case describes a young female patient with MPNST located in the dorsolumbar region and metastatic spread to the lungs, along with a history of acoustic neuroma.